A Processual Approach towards Studying Management Accounting Change - Hassan Yazdifar; Davood Askarany; Ahmad Nasseri; Mohammad Ali Moradi (Journal of Accounting, Business and Management (JABM), 2012)
The issue of organizational change has assumed central importance in business and management related research during the last two decades. Management accounting is no exception. Change in management accounting systems and techniques, the roles of accountants in business and, more generally, change in the shape of the finance function have particularly been the subjects of much debate in recent decades. This paper reviews two prominent approaches to change namely planned and processual approaches and concludes that a processual approach provides a richer and more enhanced understandings of management accounting change.